Intestinal carriage of vancomycin‐resistant Enterococcus spp. among high‐risk patients in university hospitals in Serbia: first surveillance report - Ana Janjusevic; Ljiljana Markovic Denic; Rajna Minic; Anita Grgurevic; Ivana Cirkovic (BMC, 2021)
Abstract Background The screening for intestinal carriage of vancomycin-resistant Enterococcus spp. (VRE) among high risk patients in the Balkan region and molecular epidemiology of VRE is insufficiently investigated, yet it could be of key importance in infection control. The aim of this study was to provide baseline data on VRE intestinal carriage among high-risk patients in Serbian university hospitals, to determine the phenotypic/genotypic profiles of the isolated VRE, to obtain knowledge of local resistance patterns and bridge the gaps in current VRE surveillance. Methods The VRE reservoir was investigated using stool samples from 268 inpatients. Characterization of isolated VRE stains consisted of BD Phoenix system, genotypic identification, glycopeptide and quinupristin-dalfopristin (Q-D) resistance probing, virulence gene (esp, hyl, efaA, asa1, gelE, cpd) detection and MLVA. Biofilm formation was evaluated by the microtiter plate method. Results VRE carriage prevalence among at-risk patients was 28.7%. All VRE strains were vanA positive multidrug-resistant Enterococcus faecium (VRfm), harboring ermB-1 (38.9%), esp (84%), efaA (71.2%), hyl (54.5%), asa1 (23.4%), gelE and cpd (11.6%) each. Ability of biofilm production was detected in 20.8%. Genetic relatedness of the isolates revealed 13 clusters, heterogeneous picture and 25 unique MTs profiles. Conclusion The obtained prevalence of VRE intestinal carriage among high-risk inpatients in Serbia is higher than the European average, with high percentage of multidrug resistance. The emergence of resistance to Q-D is of particular concern. Close monitoring of pattern of resistance and strict adherence to specific guidelines are urgently needed in Serbia.